2017
DOI: 10.1186/s12864-016-3454-z
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of rice has reduced the occurrence of transposable elements within gene coding regions

Abstract: BackgroundTransposable elements (TEs) are prominent features in many plant genomes, and patterns of TEs in closely related rice species are thus proposed as an ideal model to study TEs roles in the context of plant genome evolution. As TEs may contribute to improved rice growth and grain quality, it is of pivotal significance for worldwide food security and biomass production.ResultsWe analyzed three cultivated rice species and their closest five wild relatives for distribution and content of TEs in their geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…A recent study showed that wild rice genomes tend to accumulate TEs in genic regions, while cultivated rice genomes show depletion of TEs from genic regions including introns [103]. This has likely occurred independently in the genomes of several cultivars [103]. This convergent loss of genic TE sequences in cultivar genomes may be a result of selective pressure against long heterochromatic TEs in the genic regions during domestication and selection (Fig 3).…”
Section: Plos Geneticsmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study showed that wild rice genomes tend to accumulate TEs in genic regions, while cultivated rice genomes show depletion of TEs from genic regions including introns [103]. This has likely occurred independently in the genomes of several cultivars [103]. This convergent loss of genic TE sequences in cultivar genomes may be a result of selective pressure against long heterochromatic TEs in the genic regions during domestication and selection (Fig 3).…”
Section: Plos Geneticsmentioning
confidence: 96%
“…A recent study showed that wild rice genomes tend to accumulate TEs in genic regions, while cultivated rice genomes show depletion of TEs from genic regions including introns [103]. This has likely occurred independently in the genomes of several cultivars [103].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Several other genes related mostly to japonica rice domestication, including qSH1, PLOG1, qSW5, GIF1, and Rc, have been cloned and functionally characterized (Kovach et al, 2007;Izawa, 2008). In such instances, simple changes in the promoter sequences of these genes altered their expression (Huo et al, 2017), while in some cases insertion of a transposon was responsible (Li et al, 2017). There were also SNPs that likely alter the key amino acids in important proteins such as enzymes (Kharabian-Masouleh et al, 2012;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation and plant breeding reduces genetic diversity and tness to environmental stresses (Roger et al, 2012). A recent whole-genome comparison of wild and cultivated rice species revealed depletion of intronic TE insertions in cultivated species (Li et al, 2017b). Gymnosperms are outcrossing species that produce large quantities of pollen and seeds, generating a genetically diverse germplasm pool for subsequent natural selection of highly adaptable seedlings.…”
Section: Discussionmentioning
confidence: 99%